Properties of Fuzzy Norm of fuzzy Bounded Operators - Kider , Jehad R.; Kadhum , Noor Ahmed (Iraqi Journal of Science, 2021)
The principal aim of this research is to use the definition of fuzzy normed spaceto define fuzzy bounded operator as an introduction to define the fuzzy norm of afuzzy bounded linear operator then we proved that the fuzzy normed space FB(X,Y)consisting of all fuzzy bounded linear operators from a fuzzy norm space X into afuzzy norm space Y is fuzzy complete if Y is fuzzy complete. Also we introducedifferent types of fuzzy convergence of operators.